2010
DOI: 10.5012/bkcs.2010.31.02.309
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrochemical Properties of Surface Modified LiMn2O4by Li-Fe Composites for Rechargeable Lithium Ion Batteries

Abstract: The surface modified LiMn2O4 materials with Li-Fe composites were prepared by a sol-gel method to improve the electrochemical performance of LiMn2O4 and were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), and transmission electron microscopy (TEM)-EDS. XRD results indicate that all the samples (modified and pristine samples) have cubic spinel structures, and XRD, XPS, and TEM-EDS data reveal the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The XPS spectra showed Mn2p 3/2 feature at 642.6 eV on the both active materials, and this values was consistent with other reports. 8 Further, the O1s peak was observed around 529.8 eV of binding energy on the both active materials. This finding indicated that the binding energies of Mn2p 3/2 and O1s were same on the surface of the NS-LMO and MS-LMO.…”
Section: Esr Measurementsmentioning
confidence: 99%
“…The XPS spectra showed Mn2p 3/2 feature at 642.6 eV on the both active materials, and this values was consistent with other reports. 8 Further, the O1s peak was observed around 529.8 eV of binding energy on the both active materials. This finding indicated that the binding energies of Mn2p 3/2 and O1s were same on the surface of the NS-LMO and MS-LMO.…”
Section: Esr Measurementsmentioning
confidence: 99%
“…Each EIS curve consists of two semicircles representing the resistance of the surface electrolyte interface (SEI) film in the high frequency and the charge-transfer resistance in the medium frequency. [21][22] The value of each resistance is determined using the equivalent circuit shown in the inset of Figure 4. The LiFePO4/5 wt % PEDOT electrode exhibits significantly lower charge-transfer and SEI film resistances (20.73 and 5.296 Ω) than pristine LiFePO4 (35.02 and 6.397 Ω).…”
mentioning
confidence: 99%